Normal echocardiographic mitral and aortic valve thickness in children. Issue 1 (21st March 2017) - Webb, Rachel H; Culliford-Semmens, Nicola; Sidhu, Karishma; Wilson, Nigel J
Abstract : Objective: We aimed to define the normal range of aortic and mitral valve thickness in healthy schoolchildren from a high prevalence rheumatic heart disease (RHD) region, using a standardised protocol for imaging and measurement. Methods: Measurements were performed in 288 children without RHD. Anterior mitral valve leaflet (AMVL) thickness measurements were performed at the midpoint and tip of the leaflet in the parasternal long axis (PSLA) in diastole, when the AMVL was approximately parallel to the ventricular septum. Thickness of the aortic valve was measured from PSLA imaging in systole when the leaflets were at maximum excursion. The right coronary and non-coronary closure lines of the aortic valve were measured in diastole in parasternal short axis (PSSA) imaging. Results were compared with 51 children with RHD classified by World Heart Federation diagnostic criteria. Results: In normal children, median AMVL tip thickness was 2.0 mm (IQR 1.7–2.4) and median AMVL midpoint thickness 2.0 mm (IQR 1.7–2.4). The median aortic valve thickness was 1.5 mm (IQR 1.3–1.6) in the PSLA view and 1.4 mm (IQR 1.2–1.6) in the PSSA view. The interclass correlation coefficient for the AMVL tip was 0.85 (0.71 to 0.92) and for the AMVL midpoint was 0.77 (0.54 to 0.87). Conclusions: We have described a standardised method for mitral and aortic valve measurement in children which is objective and reproducible. Normal ranges of left heart valve thickness in a high prevalence RHD population are established. These results provide a reference range for school-age children in high prevalence RHD regions undergoing echocardiographic screening.